The Making of Indonesian Education: An overview on Empowering Indonesian Teachers - Teuku Zulfikar (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2009)
Education is one of the fundamental priorities of nation building. For this reason, the Indonesian government continuously seeks to improve the quality of its education. Empowering education can be done using many strategies, such as reforming school curricula or school systems or both. This article approaches the improvement of Indonesian education from a different angle, by considering teachers and the teaching profession. Before proposing an agenda for improving teachers, the article considers two main problems of Indonesian teachers: the practice of teacher-centred classroom pedagogy; and the emphasis on rote learning in the classroom. In response to these phenomena, this article suggests two main factors responsible for the persistence of such teaching styles: institutional cultures and the nature of assessment systems in Indonesian schools. This article has three recommendations to help Indonesian teachers improve. However, the author is aware that the agendas for improvement are complex and institutional reforms are needed; for example, the reform of teacher recruitment; teacher evaluation and also the reform of assessment systems. This article includes a discussion of what makes for a good teacher, which will help Indonesian teachers to gain an insight to their profession, and a discussion of the changes that could be made to enable the quality of teaching to improve.